A New TBX5 Loss-of-Function Mutation Contributes to Congenital Heart Defect and Atrioventricular Block - Zhang, Yan; Sun, Yu-Min; Xu, Ying-Jia; Zhao, Cui-Mei; Yuan, Fang; Guo, Xiao-Juan; Guo, Yu-Han; Yang, Chen-Xi; Gu, Jia-Ning; Qiao, Qi; Wang, Jun; Yang, Yi-Qing (International Heart Journal, 2020)
Congenital heart defect (CHD) represents the most common birth deformity, afflicting 1% of all births worldwide, and accounts for substantial morbidity and mortality. Increasing evidence highlights the pivotal roles of genetic etiologies in the pathogenesis of CHD, and pathogenic mutations in multiple genes, including TBX5 encoding a cardiac core transcription factor key to cardiovascular morphogenesis, have been involved in CHD. However, due to pronounced genetic heterogeneity of CHD, the genetic determinants underlying CHD in most cases remain obscure. In this investigation, by sequencing analysis of the coding exons and flanking introns of the TBX5 gene in 198 unrelated patients affected with CHD, a novel heterozygous mutation, NM_000192.3: c.692C>T; p. (Pro231Leu), was identified in an index patient with familial double outlet right ventricle (DORV), ventricular septal defect (VSD), and atrioventricular block (AVB). Genetic analysis of the proband's pedigree showed that the mutation co-segregated with the diseases. The missense mutation, which altered the amino acid conserved evolutionarily, was absent from 266 unrelated healthy subjects. Functional analyses with a dual-luciferase reporter assay system unveiled that the Pro231Leu-mutant TBX5 was associated with significantly reduced transcriptional activity on its target genes MYH6 and NPPA. Furthermore, the mutation disrupted the synergistic transactivation between TBX5 and NKX2-5 as well as GATA4, two other transcription factors causally linked to CHD. This study firstly links TBX5 loss-of-function mutation to familial DORV, VSD, and AVB, which provides novel insight into the mechanism underpinning CHD and AVB, suggesting potential implications for genetic evaluation and individualized treatment of patients affected by CHD and AVB.